HRSUD: Hybrid Roadside Unit Deployment System to Improve Vehicular Communication in VANET - Shrivastava, Prashant Kumar; Kamble, Megha; Shrivastava, Priya; Sharma, Mayank; Singh Tomar, Ranjee (2021 10th IEEE International Conference on Communication Systems and Network Technologies (CSNT), 2021)
Vehicular networks use roadside units (RSUs) to increase vehicles' communication capability to relay tracking messages and/or provide vehicle, driver or passenger Internet access. Unfortunately, wireless signal communication inside vehicle networks is primarily influenced by buildings as well as other barriers (e.g. urban installations) In addition, some applications, especially security apps, require fast and effective transmission of alert data to emergency services as well as traffic authorities. However, communicating in car conditions is not always feasible, even with several hops, because there is no connection. An efficient, creative, cost effective and all-purpose RSU implementation policies should be introduced in order to overcome the problem of signal propagation as well as delayed recognize time problems. In this document we suggest the Hybrid Roadside Unit Deployment (HRSUD) framework, which incorporates fuzzy possibility c- means as well as genetic algorithms. The network coverage is provided by a fuzzy possibility c- means (FPCM) clustering. The genetic algorithm is able to provide an RSU deployment automatically suitable for any particular road map configuration. Our simulation results show that the HRSUD introduced decreases alert response cost and enhancing the ability to communicate in a number of intensity and difficulty scenarios and the time to notify emergency security services in dangerous situations. There are works on movement of units, distance measure, transmission time. From the simulation we get optimum results in terms of throughput, packet delivery ratio, and network delay and packet drop rate.